Identifikasi Potensi Interaksi Obat Pada Pasien Rawat Inap Penyakit Dalam Di RSUD Dr. Moewardi Tahun 2014 - Widyaningrum, Ristia; , Dra. Nurul Mutmainah, M.Si., Apt (2016)
Patients with internal diseases are usually treated by a combination of more than two drugs that causes potential drug interactions. Patients who suffer from the internal disease usually suffer from more than one disease. In this case, more drugs combinations are given and this will lead to the higher potential incidence of drug interactions. The purpose of the study was to identify the potential drug interactions of hospitalized patients with internal disease at X hospital in 2014. This study is an observational research. The data were collected retrospectively and the data was analyzed descriptively by using database of www.drugs.com/drug_interactions. The sampling technique was done purpossively. Hospitalized patients with internal disease taken as the sample of this study were diseases with highest incident in 2014. Five serious internal disease included in this study were non-insulin dependent diabetes mellitus, anemia, sepsis, congestive heart failure and pneumonia. Out of 100 patients, there were 92 patients (92%) who had the potential to experience drug interactions. The potential drug interactions seriousness at moderate level were 322 cases (69.75%), minor level were 96 cases(20.17%), and major level were 48 cases (10.08%). The most frequent drug interactions happened was furosemide with ceftriaxone, 24 cases (7.23%). The pharmacodynamic mechanism of potential drug interactions happened was 329 cases (69.12%), pharmacokinetic mechanism 74 cases (15.55%), and unknown mechanism 73 cases (15.33%)